Syndecan-4 interacts directly with β-parvin and regulates the ILK-PINCH-β-parvin complex, the β-parvin-β-PIX-Rac1 axis, and cardiomyocyte geometry in a sex-dependent manner - Mathiesen, Sabrina Bech; Støle, Thea Parsberg; Romaine, Andreas; Lunde, Marianne; Martinsen, Marita; Aronsen, Jan Magnus; Sjaastad, Ivar; Louch, William E.; Christensen, Geir; Carlson, Cathrine Rein (Frontiers in Cell and Developmental Biology, 2025)
Syndecan-4 is a ubiquitously expressed transmembrane proteoglycan that links the extracellular matrix to intracellular protein networks. It is located at stress-sensing structures in cardiomyocytes, including costameres and Z-discs, and in male mice, it is involved in the hypertrophic response to cardiac pressure overload. We have recently found female syndecan-4 KO cardiomyocytes, without challenge, to be smaller in area. Smaller cardiomyocytes with elongation defects have been observed in animal models with β-parvin deficiency, where the loss of this mechano-sensor disrupts the guanine nucleotide exchange factor (GEF) β-PIX-GTPase Rac1 axis, which is essential for proper cell elongation. β-parvin, together with integrin-linked kinase (ILK) and particularly interesting new cysteine-histidine-rich protein (PINCH), constitutes the IPP complex (ILK-PINCH-parvin), which is part of the integrin consensus adhesome. Interestingly, in a previous large cardiac interactome study, we have identified β-parvin, as well as ILK, β-PIX, and Rac1 as potential syndecan-4 partners. To better understand the syndecan-4-β-parvin association, we mapped their interaction and investigated the effect of syndecan-4 ablation on the IPP complex, the β-parvin-β-PIX-Rac1 axis, and cardiomyocyte geometry in both females and males. Interestingly, genetic ablation of syndecan-4 resulted in shorter cardiomyocytes in females only. The syndecan-4-β-parvin interaction was mapped to accessible sequences within the N-terminal, linker, and CH2 domains of β-parvin and the unique variable C2 cytoplasmic region of syndecan-4. Syndecan-4 ablation resulted in lower levels of membrane-localized β-parvin in both sexes and sex-specific differences in its associated partners ILK and PINCH, suggesting that syndecan-4 is linked to integrin signaling through the IPP complex. Finally, Rac1, known for its involvement in cell size regulation, and some of its regulators, β-PIX, RhoGDIα, and the serine/threonine kinase PAK, showed sex-specific alterations following syndecan-4 ablation. Altogether, our data suggest that syndecan-4 binds directly to β-parvin and regulates cardiomyocyte length, the IPP complex, and the β-parvin-β-PIX-Rac1 in a sex-dependent manner. These findings highlight a sex-specific role for syndecan-4 in cardiomyocyte structure, offering new insight into the molecular basis for sex differences in cardiac biology.